2006
DOI: 10.1002/ana.20763
|View full text |Cite
|
Sign up to set email alerts
|

Posterior hypothalamic activation in paroxysmal hemicrania

Abstract: These activated subcortical structures may play a pivotal role in the pathophysiology of this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
1
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(139 citation statements)
references
References 71 publications
2
129
1
7
Order By: Relevance
“…Finally, we observed significant unilateral activation in the RN after heat stimulus to the V2A (Fig. 4), similar to that reported after experimental visceral and somatic pain in healthy subjects (Bingel et al, 2002;Dunckley et al, 2005) and in paroxysmal hemicrania (Matharu et al, 2006). A role for the RN in neuropathic pain is unknown, but it has been suggested to be involved in withdrawal behavior or execution of movements (Keifer and Houk, 1994) and the sensorimotor integration of nociceptive information involves via a spino-rubral circuit (Steffens et al, 2000).…”
Section: Thalamus and Cortex (Si)supporting
confidence: 85%
“…Finally, we observed significant unilateral activation in the RN after heat stimulus to the V2A (Fig. 4), similar to that reported after experimental visceral and somatic pain in healthy subjects (Bingel et al, 2002;Dunckley et al, 2005) and in paroxysmal hemicrania (Matharu et al, 2006). A role for the RN in neuropathic pain is unknown, but it has been suggested to be involved in withdrawal behavior or execution of movements (Keifer and Houk, 1994) and the sensorimotor integration of nociceptive information involves via a spino-rubral circuit (Steffens et al, 2000).…”
Section: Thalamus and Cortex (Si)supporting
confidence: 85%
“…Although cluster headaches have been reported to respond to indomethacin, 8 this feature usually suggests paroxysmal hemicrania 2 and raises the possibility that this phenomenon may be relevant to the trigeminal autonomic cephalgias (TAC) as a group, all of which are associated with the posterior hypothalamus. 9 The sympathetic nervous system is believed to be associated with TAC in a passive manner 1 ; however, in some cases, there is evidence of sympathetic dysfunction before the onset of TAC, 10 suggesting that sympathetic underactivity may underlie TAC pathogenesis. If TAC pain is dependent on low sympathetic tone, theoretically the episode could be reversed by the increase in sympathetic activity accompanying sexual activity and, specifically, orgasm.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that a previous PET study found significant activation of the contralateral posterior hypothalamus in untreated PH, 13 whereas ipsilateral posterior hypothalamic activation has been demonstrated during a cluster headache attack. 11 Nevertheless, ipsilateral hypothalamic stimulation was effective in the patient with PH, as already noted, 64 just as it is in cluster headache.…”
Section: Sunct Syndrome and Paroxysmal Hemicraniamentioning
confidence: 87%
“…11 This latter area was initially thought to be activated only in cluster headache, and was proposed as the cluster generator. 11 It was subsequently shown, however, that this hypothalamic area is also activated during SUNCT, 12 PH, 13 and hemicrania continua. 14 Hemicrania continua is a strictly unilateral headache accompanied by ipsilateral oculofacial autonomic symptoms not now considered to be a trigeminal autonomic cephalalgia, because of its long-lasting pain.…”
Section: Rationale For Hypothalamic Stimulation In Headachementioning
confidence: 99%